Forest vegetation cover in Bu Gia Map National Park, Vietnam - Hai Chau, Mai Hải Châu; Thi Ngoan, Tran; Van Phu, Nguyen; Van Cuong, Le; Trong Phu, Nguyen; Phuc Da, Huynh; Viet Hung, Dang (Journal of Forestry Science and Technology, 2024)
Understanding the composition of tree species is essential for establishing conservation priorities. Bu Gia Map National Park is in the tropical rainforest zone of Southeast Vietnam. This paper is to analyse and assess tree species composition and biodiversity conservation in Bu Gia Map National Park. The diversity of plant species in Bu Gia Map National Park was studied to provide baseline information for conservation and sustainable management processes that will prolong the life of National Park. The results obtained from the study conducted on the plant species composition and forest vegetation in this national park revealed a total of 786 species, spanning 430 genera and 132 families, across three divisions of vascular plants: Polypodiophyta, Pinophyta, and Magnoliophyta. Among these are 300 species of timber plants, 270 species of medicinal plants, 62 species of edible plants, 74 species of ornamental plants, 40 species of industrial plants, 28 species of fiber plants, and 12 species of plants with unknown use. Notably, during the investigation period, Goniothalamus vietnamensis Ban and Myxopyrum smilacifolium Blume were newly recorded in the forest vegetation of Bu Gia Map National Park. The study also describes a variety of forest vegetation in the area, identifying two major forest vegetation types within Bu Gia Map National Park.